2018
DOI: 10.1007/s11695-017-3104-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Severe Obese Patients Undergoing Surgery for Obesity and Weight-Related Diseases

Abstract: BackgroundObesity is a worldwide disease related to genetic, environmental, and behavioral factors, and it is associated with high rates of morbidity and mortality. Recently, obesity has been characterized by a low-grade inflammatory state known as inflammome indicated by chronic increases in circulating concentrations of inflammatory markers. The purpose of this study was to evaluate the effect of weight loss induced by surgery for obesity and weight-related diseases on pro-inflammatory cytokine (TNF-α) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
(54 reference statements)
4
31
0
Order By: Relevance
“…We found that the reductions in LAR were driven primarily by an increase in adiponectin rather than a reduction in leptin, and these changes were proportional to the reduction in weight after surgery, consistent with the Unamuno study. The changes we observed in leptin and adiponectin concentrations were less than those described after bypass bariatric surgery 3,6,7 and are more consistent with those previously described after banding 8 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that the reductions in LAR were driven primarily by an increase in adiponectin rather than a reduction in leptin, and these changes were proportional to the reduction in weight after surgery, consistent with the Unamuno study. The changes we observed in leptin and adiponectin concentrations were less than those described after bypass bariatric surgery 3,6,7 and are more consistent with those previously described after banding 8 .…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, adiponectin reduces circulating free fatty acids by increasing tissue fat oxidation: Adiponectin levels tend to be lower in individuals with obesity 14 . Several studies have described reductions in leptin and increases in adiponectin in adults with severe obesity undergoing bariatric surgery 3 , 6 8 , 15 . Recently, investigators described changes in the adiponectin: leptin ratio (ALR) in a cohort of 25 Spanish adults with type 2 diabetes who underwent Roux-en-Y gastric bypass 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the percentage of functional β pancreatic cells, we noticed a statistically significant decrease: the preoperative arithmetic mean is 144.2 (± 74.9) and the postoperative, 86.0 (± 34.9) (p < 0.0001, Student test for dependent batches) (Figure 8). The gender distribution results of this study fall within the limits observed in the literature [17]. Thus, the ratio between genders, clear-cut suitable for the feminine gender, follows the trend observed in similar studies.…”
Section: Percentage Of Functional β Pancreatic Cells Pre-and Postopersupporting
confidence: 90%
“…The prevalence of obesity has increased significantly in the last three decades, being considered a pandemic that affects 1.9 billion people worldwide. In developed and developing countries, overweight and obesity are considered public health problems and have a high mortality rate due to associated risk factors [1].…”
Section: Introductionmentioning
confidence: 99%